Relation between water permeability and chloride diffusivity of concrete under compressive stress: Experimental investigation and mesoscale lattice modelling. (18th January 2021) - Tran, T.T.; Pham, D.T.; Vu, M.N.; Truong, V.Q.; Ho, X.B.; Tran, N.L.; Nguyen-Sy, T.; To, Q.D.
Highlights: Transport properties of concretes under compressive stress are investigated. Water permeability is measured by tests on hollow cylindrical specimens. Bespoke test setup is used to measure the rapid chloride permeability. Hydro-damage lattice model is proposed to assess stress induced changes in transport properties. Relation between water permeability and chloride diffusivity is proposed. Abstract: This paper presents experimental investigations and a lattice modelling of the water permeability and chloride diffusivity of concrete under compressive stress and then proposes relationships between these two transport properties. Two representative ordinary concretes usually used in structures, subjected to compressive loading and water seepage or chloride contact, are considered. Water permeability tests were performed on hollow cylindrical samples in which the water diffuses in the radial direction through the sample thickness from the outer to inner surfaces under three different pressure gradients 3, 4 and 5 atm. Four compressive stresses (20%; 40%; 60% and 80% of the compressive strength) were applied on the sample top surface during the water permeability measurement. Rapid Chloride Permeability Testing (RCPT) is used to evaluate the chloride diffusivity. RCPT was carried out on cylindrical cores under four different stress levels (0; 25%; 50% and 75% of the stress at ultimate load). Mesoscale hydro-mechanical lattice modelling is proposed to model the fluid flow and chloride ingress in concrete under stress. In such a model, concrete includes three constituents: cement, aggregates and interfacial transition zone (ITZ). A softening damage model is employed to describe the behaviour of the cement matrix and the ITZ, while the aggregates are assumed to be elastic. Hydro-mechanical parameters of concrete components are calibrated from the experimental results of both water permeability and chloride diffusion tests. The proposed model allows extrapolating the experimental results for higher compressive stress. A relation between water permeability and diffusivity coefficients is resulted from both experimental and numerical investigations for a large range of compressive stress.